Social conflict and social assimilation: Constitution, politics and administration in India - Sharma, Rajvir (2002)
The article analyses the factors that cause social tension, particularly in Indian context. It exhaustively deal with the state response to social tension through accommodation politics, and development planning, policies and programmes for the welfare of various deprived segments. It shows how the state has created political mechanisms to assimilate the weaker sections in the political process and to make them benefit from a number of welfare and development policies. The author emphasises a greater role of nation's social, cultural and economic structure and values to face the challenges of social conflict. - Reproduced.
Keywords: India - Politics and government; Politics and government; India - Constitution; Constitutions; Social conflicts - India; Social conflicts